Analisis Komparatif Kebijakan Ekonomi Sektor Perikanan Pada Tahun 2010 – 2017 - Lailan Safina Hsb; Salman Paris (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2020)
This study aims to determine the role of government in improving the fisheries sector of the year 2010 – 2017. Considering that Indonesia is the largest maritime country in the world so it should  contribute greatly to the formation Indonesia’s GDP. The purpose of this study is divided into 2 objectives namely : (1) comparing the policies of the government in increasing the potential for fisheries in Indonesia in 2010 -2017. (2). See the development of the fisheries I Indonesia since 2010 – 2017 through value Indonesia GDP, export fisheries and production. The data used is secondary data with data sources through The Central Statistics Agency (BPS) website. Basically it turns out that fisheries sector has not been able to make large contribution to Indonesia GDP, although there have been many policies undertaken by government to improve the fisheries sector.